1991
DOI: 10.1063/1.349733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn incorporation on the growth mechanism of sprayed SnO2 films

Abstract: In order to probe into the growth mechanism of sprayed SnO2 films, the films were deposited with different Sn concentrations in the precursor solution. The orientational properties were determined using grazing incidence x-ray diffraction. The preferred growth changed from [110] to [200] direction as the Sn incorporation was increased. Such a change in growth can be anticipated from structure factor calculations. The compositional analysis was done using x-ray photoelectron spectroscopy. The Hall effect measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 17 publications
4
32
0
Order By: Relevance
“…17 Thus the non-stoichiometric tin dioxide layer likely impacts the conductivity of the layer. 18 However, SnO has a higher free energy of formation (264kJ/mol) than that of SnO 2 , so the film may not be thermodynamically stable if the monoxide is present. The intermediate layer consists of a mixed tin oxide and titanium oxide.…”
Section: Resultsmentioning
confidence: 99%
“…17 Thus the non-stoichiometric tin dioxide layer likely impacts the conductivity of the layer. 18 However, SnO has a higher free energy of formation (264kJ/mol) than that of SnO 2 , so the film may not be thermodynamically stable if the monoxide is present. The intermediate layer consists of a mixed tin oxide and titanium oxide.…”
Section: Resultsmentioning
confidence: 99%
“…The prominent (200) peak in S1-S3 and the emergence of a stronger (110) peak in S4-S6 is mostly likely related to the concentration of the precursor materials used. It is known that the films with a preferred orientation of (200) require high halogen rich gases [20,21]. Under the growth conditions, the S1-S3 having a higher concentration of TFAA solution will result in more gaseous polar molecules and will adsorb on polar F-(101) surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it has also been reported that the structural, morphological, optical and electrical properties of FTO thin films critically depend on the type of dopant and their concentration, calcination conditions (in aerobic and anaerobic) and also plasma/UV treatment. [12][13][14] Therefore, as reported in previous contributions, optimizing these properties of FTO film will certainly be beneficial for perovskite solar cells in regard to enhancing overall performance. [15][16][17][18][19] In particular, further optimization of the FTO films, by varying dopant concentrations, heat treatment conditions (such as variation of type of gas, in particular, replacement of air with N 2 in the oven) followed by plasma or UV treatment and then by carefully monitoring the variation of crystallinity, surface morphology, optical and electrical properties, will allow to further tune these properties deemed for perovskite solar cells.…”
Section: Introductionmentioning
confidence: 95%
“…To note, the actual incorporation of Fluorine into the film was expected to be very low due to the high volatility of fluorine compounds produced during the film deposition, as reported in earlier studies. 13,14 Also, after calcination only under air, a set of samples was further exposed to low temperature plasma, which was carried out in atmospheric pressure Dielectric Barrier Discharge (DBD) in Argon. The gas flow rate was 2 l/min.…”
Section: A Film Preparationmentioning
confidence: 99%
See 1 more Smart Citation